De interpretado a intérprete: a escuta do sujeito no processo de reescrita - (:unkn) unknown (Universidade Estadual de Ponta Grossa, 2024)
The present research is grounded in the Interactionist framework of Language Acquisition formulated by Cláudia de Lemos (2002), which posits that the subject's relationship with language is continuously subject to changes and shifts within the structure encompassing the subject, the other, and language-discourse. In this perspective, the process of acquisition is understood as a subjectivation process wherein the subject transitions from the position of infans — the one who does not speak — to that of a speaker. This transition involves changes mediated by listening, in the subject’s relationship with the other, with language, and with their own speech. Aligned with other researchers in the field of written language acquisition who share this theoretical perspective, this study seeks to analyze rewriting practices in children’s texts produced within the school context. The objective is to investigate the child’s relationship with writing and with the other — the teacher — in rewriting activities conducted with 6th-grade students in elementary education. To achieve this, the study aims to examine the signs of the student’s listening in relation to the teacher’s discourse, the language, and their own text during the rewriting process; to analyze the effects of the teacher’s discourse on the second version of the text; and to understand the changes occurring in the text when the student transitions from the position of being interpreted by the teacher to assuming the role of self-interpreter.The productions are organized into three stages: (i) texts produced by the students in response to a production prompt; (ii) correction of the texts; and (iii) the rewritten version. Based on the listening process conducted by the student — of the teacher's interventions and their own discourse — it was possible to observe the positional shifts of the student, from being interpreted to becoming the interpreter of their own text. This allowed for reflection on the movements of the child’s return to their own writing.
Keywords: Reescrita; Escuta; Sujeito; Língua; O outro; Rewriting; Listening; Subject; Language; The other; CNPQ::LINGUISTICA, LETRAS E ARTES